Social media marketing and influencer marketing in digital age – A comparative study - Shenoy, Swathi; Bhojgar, Deeksha; Megha, Megha; Chethanraj (BOHR International Journal of Advances in Management Research, 2025)
Social media platforms have revolutionized marketing strategies, providing businesses with unprecedented opportunities to reach and engage with their target audiences. Two prominent marketing techniques that have gained significant popularity are social media marketing and influencer marketing. This comparative study aims to analyze and evaluate the effectiveness, benefits, challenges, and customers associated with these two approaches in the context of the digital age. This comparative study looks at social media marketing on consumer behavior in comparison with influencer marketing. In this study, we came to know that both marketing is preferable because the respondents are using social media marketing, and sometimes their product choice is based on the advertisement. Influencer marketing is also affecting consumer behavior. It is observed that the majority of respondents use digital marketing platforms frequently. Instagram, WhatsApp, Facebook, and Snapchat are actively using social media channels and have a powerful impact on people, especially on the young generation.